Five‐Year Incidence of Hospital‐Based Emergencies Related to Acute Recreational Intoxication in Minors. (27th August 2019) - Sanvisens, Arantza; Sanjeevan, Irina; Zuluaga, Paola; Túnez, Adrià; de Francisco, Antonio; Papaseit, Esther; García‐Eroles, Luis; Muga, Robert
Abstract : Background: Alcohol or other drug (AOD) intoxication in minors is a public health challenge. We characterized underage patients admitted to an emergency department (ED) with acute, recreational AOD intoxication. Methods: We conducted a 5‐year (2012 to 2016) analysis of minors admitted to the only hospital‐based pediatric ED in an urban area. Episodes of AOD intoxication were selected using ICD‐9‐CM diagnostic codes. Sociodemographics, substance use and clinical characteristics, laboratory parameters, and discharge dispositions were collected through the revision of clinical charts. Results: A total of 266 admissions related to recreational AOD intoxication in 258 patients occurred during the study period. Among the 258 patients, 127 (49.2%) were men, median age 16 years [IQR: 15 to 17 years], and 234 (90.7%) of episodes were alcohol‐related. At admission, 202/256 (78.9%) patients had a Glasgow Coma Scale ≥ 13 points, the median systolic and diastolic blood pressure was 109 mmHg (IQR: 101 to 118 mmHg) and 67 mmHg (IQR: 60 to 73 mmHg), respectively, and the median blood glucose level was 112 mg/dl (IQR: 99 to 127 mg/dl). Only 72/258 (27.9%) patients underwent urine screening (22/72 (30.5%) were positive for cannabis), and only 30/258 (11.6%) were tested for blood ethanol (median: 185 mg/dl, IQR: 163 to 240 mg/dl). There was a trend in admissions occurring early in the morning of weekend days, and 249 (96.5%) patients were discharged home the day of admission. Conclusions: Though the severity of AOD intoxication seems to be mild to moderate, assessment of substance exposure is low and may underestimate polydrug use in underage populations. Abstract : The manuscript describes a series of underage patients with alcohol and/or substance intoxications admitted to an Emergency Department in metropolitan Barcelona, Spain, between 2012 and 2016. We focus on clinical severity and performance of pediatricians in a large series of acute intoxications during 5 years. The study highlights the need to systematically implement screening, assessment and retention in care.